PERLAKUAN ZAKAT SEBAGAI PENGURANG LANGSUNG TAX INCOME DENGAN PERLAKUAN ZAKAT SEBAGAI PENGURANG PENGHASILAN KENA PAJAK - Wahyu Afrilia Mawardianti; Afifudin Afifudin; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTIONThis research is entitled Treatment of Zakat as Direct Tax Income Reduction withthe Treatment of Zakat as a Taxable Income Reduction. The purpose of this studywas to analyze the difference between zakat treatment as a direct deduction of taxincome by treating the contract as a deduction from taxable income. The type ofresearch used in this study is qualitative research and using a comparative studyapproach. The location of this research is Lazis of Jami Mosque, Malang City.The results of this study indicate that there are differences between the twotreatments. In the first treatment, the expenditure on zakat and tax obligations issmaller than the second treatment. The difference in the percentage of the twotreatments is 1.475%. The final analysis of research is that there is a positivecorrelation between zakat and tax.Keywords: Zakat, Income Tax, Taxable Income Deduction.